ENVIRONMENT AND ANIMAL SOURCES OF LEPROSY TRANSMISSION: LITERATURE REVIEW - Susilawati, Susilawati; Hasyim, Hamzah; Sutari, Sutari; Syafrianto, Syafrianto; Syofyanengsih, Syofyanengsih; Kusuma, Titin; Syafni, Eliza (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Efforts in the prevention and treatment of leprosy have improved, but until now leprosy is still difficult to be eliminated so that it is still a problem in the world of health. The incidence of new leprosy patients has not decreased, although the prevalence of leprosy continues to decline through the WHO program, namely multi-drug therapy (MTD). Several new cases have been found without involving any contact history. It is suspected that there is a contribution from sources other than humans, namely non-humans such as animals and the environment. This article discusses the sources of transmission of M. leprae from animals and the environment. Research using literature review is limited to the last 10 years by reviewing 8 relevant journals about sources of transmission and modes of transmission from the environment and non-humans in Mycobacterium leprae. This article has been filtered from 35 articles sourced from the Pubmed, NCBI, Plos One and Science Direct databases, then there are 23 articles that are not relevant, so 12 articles were reviewed. Based on the results of a review article that the source of leprosy transmission came from animals, it was found in Rhodnius prolixus, Dasypus novemcinctus and red squirrels, while chimpanzees and monkeys were not the source of M. leprae transmission. In the environment where M. leprae is commonly found in the soil.Â